PENGARUH PEMBELAJARAN DIFERENSIASI KONTEN TERHADAP HASIL BELAJAR PPKn PADA MATERI KEBERAGAMAN BUDAYA DI INDONESIA KELAS IV SD GMIT NO. 7 OEBUFU KOTA KUPANG - Datire, Virna Wasti; Nitte, Yulsy Marselina; Mbuik, Heryon Bernard (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the problem of low student learning outcomes in the subject of Civic Education (PPKn), especially on the topic of cultural diversity in Indonesia, which is caused by teacher-centered learning strategies that do not accommodate diverse student learning styles. The purpose of this study is to determine the effect of content differentiation learning on the learning outcomes of fourth grade students at SD GMIT No. 7 Oebufu, Kupang City. This study uses a quantitative approach with a quasi-experimental design using a pretest-posttest design of a non-equivalent control group. The sample consisted of 34 fourth-graders who were divided into an experimental class and a control class. Data were collected through observation, testing, and documentation, and analyzed using normality, homogeneity, and independent sample t-tests. The results showed a significant improvement in student learning outcomes, with the average score increasing from 65.29 in the control class to 88.53 in the experimental class. The results of the independent sample t-test showed significant differences between the two groups (sig. 0.000 < 0.05). It can be concluded that content differentiation learning has a significant positive influence on student learning outcomes in the subject of Citizenship, especially on the topic of cultural diversity. Therefore, this approach is recommended to create a more inclusive, student-centered, and effective learning environment. Keywords: Content Differentiation Learning, Learning Outcomes, Civic Education